Embodied Religious Belief: The Experience of Syahadatain Sufi Order in Indonesia - Mahatma, Masmuni; Saari, Zarrina (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
Several types of research on religion in Indonesia emphasise more on religious knowledge and belief and less on other approaches such as material aspects.Â  Religion is always related to material aspects such as mosque buildings, veils or robes for prayer, or holy water obtained from grave visitors. This study uses embodiment approach and material theory of religion to the imposition of special fashion in prayer that gives consequences on awareness and attitude of a new morality in-group cohesion. This study is a case study through participatory observations and interviews of new members of Syahadatain congregation, Cirebon, Indonesia for three years.Â  The result of the study shows two significant findings namely first, the establishment of rituals through special fashions exerts an influence on discursive awareness and moral behaviour; and second, the driving factor of the emergence of new moral behaviour from the practice is the social gaze. This study recommends the need for the study of material artifacts such as clothing can be an alternative to the study of religion in Indonesia using the embodiment approach.